2004
DOI: 10.1002/chin.200422186
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antimalarial Constituents from the Roots of Eurycoma longifolia.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 1 publication
1
64
0
6
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12] It is a popular herb used by many local races of Malaysia and mainly used as aphrodisiac, antipyretic and anti-malarial remedy. [39] Not surprisingly, Jah Hut people often use it as an aphrodisiac remedy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12] It is a popular herb used by many local races of Malaysia and mainly used as aphrodisiac, antipyretic and anti-malarial remedy. [39] Not surprisingly, Jah Hut people often use it as an aphrodisiac remedy.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the only source of income, but also an extension anti-hyperglycemic, anti-malarial, antiproliferative, anti-schistosomal, anxiolytic and aphrodisiac activities are found in both in vivo and in vitro studies. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Jah Hut people often use M. citrifolia to treat boils by topical application of leaves or fruits. This coincides with pharmacological validation, since boils (impetigo, folliculitis, furuncles, or carbuncles) are often caused by Staphylococcus aureus; M. citrifolia possess anti-bacterial properties to counter it.…”
mentioning
confidence: 99%
“…Kuo et al [67] found that among the isolates from the roots of Eurycoma longifolia, eurycomanone (137) and pasakbumin B (138) [68] …”
Section: Simaroubaceae Familymentioning
confidence: 99%
“…Certain studies report that pharmacologically, E. longifolia Jack. contains anticancer compound (Nurhanan et al 2005;Tee et al 2007), anti-bacteria (Farouk & Benafri 2007), osteoporosis therapy for men (Effendi et al 2012), cyto-toxic (Kuo et al 2003;Kuo et al 2004), aphrodisiac (Ang et al 2003;, antileukemia, anti-malaria, and dysentery (Chan et al 2005). Due to its various benefits, there has been a substantial increase in its demands for medicinal ingredients.…”
Section: E Longifoliamentioning
confidence: 99%